Humidity-sensing studies of cerium oxide nanoparticles synthesizedby non-isothermal precipitation - Khadse, V. R.; Thakur, Sharada; Patil, K. R.; Patil, Pradip (Sensors and Actuators B-Chemical, 2014)
We report the fabrication of a highly sensitive and fast humidity sensor based on cerium oxide (CeO2) nanoparticles, which were prepared at low cost via a simple non-isothermal precipitation method. The asprepared CeO2 nanoparticles were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy( TEM) and the results indicated the formation of face centered cubic phase of CeO2 with average crystallite size of approximately 10-12 nm. Humidity sensors based on CeO2 nanoparticles exhibit high and linear response within the whole relative humidity (RH) range of 11-97% at an operating frequency of 60 Hz. The corresponding impedance changes by approximately three orders of magnitude within the entire humidity range from 11% to 97% RH. The response and recovery times are about 2-3 and 9-10 s, respectively, when RH was switched between 11% and 97%. Furthermore, the sensors also show relatively small hysteresis, excellent reproducibility, long term stability and broad range of operation (11-97% RH). The complex impedance spectra of the sensor at different RHs and the equivalent circuit were analyzed to explore the humidity-sensing mechanism. This study demonstrates that the CeO2 nanoparticles prepared by non-precipitation method can be used as the humidity-sensing material for the fabrication of humidity sensors. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: CeO2 nanoparticles; Complex impedance spectra; humidity sensor; Non-isothermal precipitation; TEM